DIGITAL DATA MANAGEMENT IN PATHOLOGY - Babintseva, L. Yu. (Medical Informatics and Engineering, 2023)
Background. Digitalization processes are actively taking place in all spheres of human activity, associated with the saturation of the physical world with electronic and digital devices, means, systems and the establishment of electronic and communication interaction between them with the help of digital technologies. One of the information environments based on digital images of drugs is digital pathology. An overview of digital data management trends in modern pathology was made. The purpose of the study: to provide insight and summarize information about digital data management in pathology. Materials and methods. With the help of databases: Medline, Embase, PubMed, Web of Science, Cochrane Library, Cinahl etc., a theoretical analysis and generalization of information about modern digital data management in pathology, prospects for future research were carried out. Results. Large amounts of pathology data generated in clinical practice and in the course of scientific research make the task of improving the quality of their management urgent. Modern digital data management in pathology represents a technology aimed at providing personalized and targeted healthcare now and in the near future. Advances in medical information technologies are turning large volumes of multidimensional pathology data into useful information to drive the development and implementation of new approaches to diagnosis, treatment, and prevention of complex diseases. Conclusions. Trends in digital data management in pathology are related to the development of digitalization software and hardware, in particular image analysis tools, emulation of diagnostic procedures, management of large volumes of high-resolution images, as well as the implementation artificial intelligence.